Confronting the Challenges of Participatory Culture: Media Education for the 21st Century - Jenkins, Henry (The John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning, 2009)
Shifting the conversation about the "digital divide" from questions of technological access to questions about opportunities for being involved in participatory culture and acquiring the necessary skills.
https://katalog.adlr.link/Record/0-1670102483